Effect of limonene on the frontal ring opening metathesis polymerization of dicyclopentadiene. Issue 1 (3rd August 2015) - Alzari, Valeria; Nuvoli, Daniele; Sanna, Davide; Ruiu, Andrea; Mariani, Alberto
ABSTRACT: The frontal ring opening metathesis polymerization (FROMP) of dicyclopentadiene (DCPD) in the presence of limonene, using second generation Grubbs' catalysts, is reported. The effect of limonene on the amount of catalyst and the typical frontal polymerization parameters, as maximum temperature ( T max ) and velocity of the front ( V f ), is studied. In addition, the influence of limonene on the mechanical properties of the polymeric samples is reported. Finally, a deep study on the swelling properties of polymers is done. It has been demonstrated that limonene acts as both inhibitor and solvent of the catalyst. The T max, V f, T g, and Young modulus values decrease as the amount of limonene increases, and the polymer samples swell in THF depending on the amount of limonene. All results indicate that the limonene addition on FROMP of results in advantages on the polymerization reaction and its parameters and on the final polymer properties. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 63–68 Abstract : Frontal ring opening metathesis polymerization was successfully applied to the synthesis of copolymers of dicyclopentadiene and limonene. The presence of limonene was found to be crucial for many polymerization parameters and confers new and particular characteristics to polymer materials.